PERLINDUNGAN HUKUM DALAM PENYELESAIAN SENGKETA PELANGGARAN TERHADAP DANA NASABAH DI PASAR MODAL - Anita Anita; Muhammad Fachrurrazy; Muammar Arafat Yusmad; Fitriani Jamaluddin; Firman Muhammad Arif (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2023)
This research aims to analyze the form of legal protection for customers who suffer losses due to fraudulent funds in the capital market, the role and efforts of the Financial Services Authority in protecting customers in the capital market, and how Sharia economic law reviews in resolving disputes in the capital market.This type of research is normative legal research through a juridical approach which is carried out by examining various legal rules such as in Laws and Regulations No. 8 of 1995 concerning Capital Markets in Chapter X I concerning fraud, market manipulation and insider trading, as well as cases related to the capital market, namely the case of PT Sarijaya Permana Sekuritas. Related to dispute resolution in Islamic law explained in the Al-Quran surah Saad verse 26 Data collection techniques using Library Research techniques (literature study), namely a data collection technique that collects legal materials obtained from various sources such as books, journals, and online written media related to the object of discussion. The data analysis technique used is qualitative data analysis technique, namely analyzing data by collecting data, presenting data and drawing conclusions, then the data is arranged in descriptive form by describing the data that has been obtained in the form of logical sentence descriptions, then interpreted and given conclusions.The results of this study indicate that: First, legal protection of customers who suffer losses due to violations committed by securities companies can apply the return of unauthorized profits by the OJK to the Securities Company to provide loss compensation funds to customers. Second, based on Law Number 21 of 2011 OJK has a role in forming regulations for improvements in the field of capital markets including protecting customers as consumers. Third, dispute resolution in Islam can be through peace mechanisms (such), arbitration (tahkim), and courts (Al- qada).